2017
DOI: 10.3389/fcimb.2017.00146
|View full text |Cite
|
Sign up to set email alerts
|

Rabies Virus Infection Induces Microtubule Depolymerization to Facilitate Viral RNA Synthesis by Upregulating HDAC6

Abstract: Rabies virus (RABV) is the cause of rabies, and is associated with severe neurological symptoms, high mortality rate, and a serious threat to human health. Although cellular tubulin has recently been identified to be incorporated into RABV particles, the effects of RABV infection on the microtubule cytoskeleton remain poorly understood. In this study, we show that RABV infection induces microtubule depolymerization as observed by confocal microscopy, which is closely associated with the formation of the filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…A link between increased MAP2 expression and dendritic pathology in Down’s syndrome has also been established [ 37 ]. The interruption of the cytoskeleton by microtubule depolymerization is due to loss of α-tubulin caused by infection with rabies virus via the formation of an M-protein filament network [ 27 ], which confirms that rabies infection damages the cytoskeleton of the host cell and is associated with the accumulation of viral M proteins.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A link between increased MAP2 expression and dendritic pathology in Down’s syndrome has also been established [ 37 ]. The interruption of the cytoskeleton by microtubule depolymerization is due to loss of α-tubulin caused by infection with rabies virus via the formation of an M-protein filament network [ 27 ], which confirms that rabies infection damages the cytoskeleton of the host cell and is associated with the accumulation of viral M proteins.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, Song et al did not show any qualitative variation in the immunoreactivity of MAP2 in the pyramidal neurons of the hippocampus of infected mice [ 13 ]. Other studies have shown diminished immunoreactivity of MAP2 and NF-H in neurons infected in vitro [ 11 ], as well as loss of expression of MAP2 in neurons of the cerebral cortex and cerebellar peduncle [ 26 ] and loss of actin filaments in the hippocampus of mice [ 13 ] and in cell cultures [ 27 ]. It is possible that these differences are due to the type and virulence of the viral strains used in the studies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whole cell lysates were subjected to SDS-PAGE and immunoblotting as previously described [28]. Primary antibodies against YY1 (ab109237, Abcam), glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (ab8245, Abcam), TBK1 (ab40676, Abcam), phosphorylated TBK1 (pTBK1) (ab109272, Abcam), IRF3 (ab68481, Abcam), phosphorylated IRF3 (pIRF3) (ab76493, Abcam), Lamin A (ab8980, Abcam), IRF9 (ab51639, Abcam), STAT1 (14994, Cell Signal Technology), phosphorylated STAT1 (pSTAT1) (9167, Cell Signal Technology), STAT2 (72604, Cell Signal Technology), phosphorylated STAT2 (pSTAT2) (ab53132, Abcam), flag (ab18230, Abcam) and Myc (ab18185, Abcam) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies indicate that M inhibits NF-κB signaling through interactions with RelAp43 that acts to promote RABV infection [4][5][6]. The overexpression of M increases the expression of HDAC6, which increases RABV transcription and replication through microtubule depolymerization [7]. Residue 58 of M is also critical to RABV replication [8].…”
Section: Introductionmentioning
confidence: 99%